Analysis of the Factors Affecting the Nutritional Status and Health of the Elderly During the Covid-19 Pandemic - Anita; Nurlaili Ramli (Science Midwifery, 2022)
Nutritional problems are problems that may occur in the elderly which are closely related to food intake and body metabolism and the factors that influence them. Malnutrition represents a potential threat to the health of the elderly. This systematic review wants to learn more about the factors that affect the nutritional status of the elderly and the health of the elderly during the covid pandemic. This study is a systematic review using online databases, namely Scholar, ScienceDirect, ProQuest, and EBSCO. The keywords used are Nutritional Status, Health Elderly, and Covid-19 Pandemic. The selection process used the PRISMA protocol so that 15 articles were obtained that met the inclusion criteria. From the results of a review of several articles, it is known There are associations between emotional support, self-esteem support, appetite, carbohydrate intake, and health and nutritional status in older adults. There is a relationship between factors affecting nutritional needs and nutritional status in older adults, including physical activity, depression and mental status, medication, disease, and biological decline. The indirect causes of nutritional problems in the elderly are environmental factors, income and the availability of information, while the quality of living environment includes information related to living environment, income and nutritional status of the elderly and the quality of living environment. Factors that influence the nutritional status of older adults are food intake and disease, but are also influenced by physical activity and exercise habits.